Elite : high performance lessons and habits from a former Navy SEAL - Hays, Nick (Gildan, 2019)
Elite: High Performance Lessons and Habits from a Former Navy SEAL is a practical, no-nonsense guide to elevate your leadership skills and drive your team to their maximum potential.